"Student Engagement in Traditional Learning vs Online Learning - A comparative study" - Ms. Sagaljit Kaur Sekhon, Dr. Sushma Patil, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Due to the present unprecedented times, the entire world and the businesses have undergone a major change in their functionality, especially so in the Education sector undergoing a major transition from traditional learning to online learning. Due to this unprecedented shift the biggest challenge was engaging students during the course of the virtual classes. Therefore, the purpose of this study is to understand if there are any differences in student engagement for traditional and online modes of education delivery. The Student Course Engagement Questionnaire (SCEQ) was administered to college students in order to gauge their engagement with regards to skills, participation/interaction, emotions, and performance. Exploratory factor analysis presented a 2-factor solution namely Skill Engagement (SE) and Performance Engagement explaining 63% of the variance in student engagement. Furthermore, the results were analyzed using a one-way Analysis of Variance (ANOVA). The results demonstrated that there is significant difference between traditional learning and online learning for the factor skill engagement, however the same was insignificant for performance engagement for the participant students. Additionally, there was no significant relation of engagement with the demographic variables of gender, income, and residential location.